An experimental platform for studying the heteronuclear Efimov effect with an ultracold mixture of 6Li and 133Cs atoms - Lippi, Eleonora; Gerken, Manuel; Häfner, Stephan; Repp, Marc; Pires, Rico; Rautenberg, Michael; Krom, Tobias; Kuhnle, Eva D.; Tran, Binh; Ulmanis, Juris; Zhu, Bing; Chomaz, Lauriane; et al. (Few-body systems, 2024)
We present the experimental apparatus enabling the observation of the heteronuclear Efimov effect in an optically trapped ultracold mixture of 6 Li- 133 Cs with high-resolution control of the interactions. A compact double-species Zeeman slower consisting of four interleaving helical coils allows for a fast-switching between two optimized configurations for either Li or Cs and provides an efficient sequential loading into their respective MOTs. By means of a bichromatic optical trapping scheme based on species-selective trapping we prepare mixtures down to 100 nK of 1 × 10 4 Cs atoms and 7 × 10 3 Li atoms. Highly stable magnetic fields allow high-resolution atom-loss spectroscopy and enable to resolve splitting in the loss feature of a few tens of milligauss. These features allowed for a detailed study of the Efimov effect